(3OQGSGJ aj GdeTGcd GdeMGSHjI GdeYGUQI (B:s (3feGPL eMGSHjI ebJQMI (B/s - (3GdMjGdj, hdjO fGLjs ((3GdCQOf(B: s (3OGQ GdMGeO ddfTQ(B, s, 2002)
(3ELQGAGJ GdbjGS GdeMGSHj dJdhK GdHjFI(B- (3GdWQb GdeMGSHjI GdebJQMI deYGdLI JcGdja GdJdhK GdHjFj(B- (3bjGS JcGdja GdJdhK GdVhVGFj(B- (3GdWQb GdeMGSHjI GdebJQMI deYGdLI JcGdja GdJdhK GdVhVGFj(B- (3bjGS GdJcGdja GdeGdjI dJYGWj GdeNOQGJ aj GdGQOf(B- (3JcdaI GdLQjeI hCKQgG Ydi GdJfejI(B- (3eYGdLI GdJVNe hCKQg Ydi GdbhGFe GdeGdjI(B- (3eMGSHI GdehGQO GdHTQjI hJMdjd bhI GdYeds
Keywords: (3GdeMGSHI GdeYGUQIs; (3GdfeGPL GdeMGSHjIs